Language as a Medium of Transformation in Narrative Therapy: A View from Clinical Psychology Practice - Lisfarika Napitupulu; Ahmad Hidayat; Wina Diana Sari (Jurnal Gramatika, 2024)
This article presents a study on the application of narrative therapy in psychotherapy practice, clinical psychology, integrating practical experience and literature review. This study aims to explore how language functions as a tool for change in addressing psychological issues. Observations of patients in the practice room show that the patient's narrative in describing their condition is also influenced by the language used by the patient. When the narrative is changed through a dialogic process between therapist and patient, the perception of life experiences undergone by the patient also changes, reinforced by findings in the literature discussing narrative therapy. This writing is the beginning of a more structured research on narrative therapy, especially in relation to the use of language.